Critical Discourse Analysis Online News of Covid-19 Has Changed The World Of Education (Teun Model A. Van Dijk) - Mukramah; Nurhasanah Purba (Britain International for Academic Research (BIAR) Publisher, 2022)
This aims of the article is to Analysis Critical Discourse Online News of Covid-19 Has Changed the World of Education. This research is a qualitative research using the method of documentation and content analysis of media texts. The result of shows that Critical discourse analysis using the Teun A. Van Dijk method of news taken from online media, namely kompas.com, regarding the Covid-19 statement has changed the world of education. The analysis is carried out on the elements of the text which are divided into macro and micro structures. Based on the analysis that has been done, it is found that discourse fulfills most of the macro and micro elements. All elements are found in this analysis.